A Robust Regression Model for Handover Prediction In Wireless Networks - Wady, Shakhawan H.; Bakar, Kamalrulnizam A.; Ghafoor, Kayhan Z. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The recent applications of wireless networks demand high Quality of Service (QoS) and mobility management between access networks. For this reason, emergent Advances in IEEE 802.11 standards have been witnessed to achieve seamless communication between mobile nodes. However, since existing handover mechanisms have shortcomings in terms of mobility handover cost and latency, more robust handover decision approach should be considered. To this end, in this research, we propose a decision approach to accurately trigger handover process between current and next access point. The proposed approach incorporates robust regression model is to predict the received signal strength (RSS) of the wireless channel between the mobile node (MN) and the access point. Thus, the MN makes an accurate handover decision as well as layer 3 handover process occurs in advance to the one in layer 2. Our theoretical analysis and simulation results show that the proposed handover decision approach is far superior to the existing handover decision schemes in terms of handover latency and cost.